Parental styles and aggressive beliefs. The mediating role of affects. - Salavera, Carlos; Urbón, Eva; Usán, Pablo; Antoñanzas, José L. (Anales de Psicología / Annals of Psychology, 2024)
Parenting stiles (authoritative, democratic, permissive and neglectful) play a key role in personal development and can be related to aggressive beliefs and affects in the individual. In order to examine this relationship, 769 subjects (359 men; 46.68%), with an average age of 21.89 years, SD = 2.65, were assessed in terms of parenting styles, aggressive beliefs and affects; the mediating role of affects in the relationship between aggressive beliefs and parenting styles was also explored. The study revealed that these constructs are interrelated. The democratic parenting style was found to be the most widespread. In terms of gender, authoritative styles were used more often on men than on women, among which the permissive style was the most common. No significant gender differences were found concerning democratic and neglectful parenting styles. Women were revealed to be more exposed to negative affects, and aggressive beliefs were found to be more prevalent in men. Children educated according to a democratic style scored higher in positive affects and lower in aggressive beliefs. Authoritative styles tend to lead to above-average scores in positive affects and aggressive beliefs. In addition, one in five people educated according to a permissive style returns a high negative affect score, and one in four people educated according to a neglectful style yields high scores in aggressive beliefs. Finally, parenting styles were found to have a direct effect on aggressive beliefs, an effect enhanced by the mediating role played by affects. In conclusion, the study suggests that parenting styles are related to aggressive beliefs and affects. In addition, affects were shown to play a mediating role in the relationship between parenting styles and aggressive beliefs. Finally, it is worth emphasising that, owing to the far-reaching implications of parenting styles on the psychological, social and personal development of the individual, more research needs to be undertaken, not only to examine their relationship with affects and aggressive beliefs, but also with other psychological variables involved in personal development.